Fourier Series and Transformation with Integration and Summation - Shah, Yogendra Prasad (Patan Prospective Journal, 2022)
The main objective of this article is to study the basic of Fourier transformation, Fourier Series, Integration and summation. This article gives the basic idea about Integration and summation: definitions, types, use in different field, limitations and may more. In this article first reader gain general information about integral and summation, rule and regulation to used integration and summation, condition to used integration and summation and application in different field.